Environmentally sustainable catalytic asymmetric oxidations - Bryliakov, Konstantin (CRC Press, 2014)
Catalysis plays a vital role in chemical, petroleum, agriculture, polymer, electronics, pharmaceutical, and other industries. Over 90 percent of chemicals originate from catalytic processes. Toughening economic and environmental constraints have proven to be a challenge for meeting the demand of novel efficient and sustainable regio- and stereoselective catalyst systems. Environmentally Sustainable Catalytic Asymmetric Oxidations provides a comprehensive overview of existing ecologically friendly catalyst systems for various asymmetric oxidation processes. Topics include:A survey of existing tr.